Is Blood Thicker Than Water? A Study of Stewardship Perceptions in Family Business - Davis, James H.; Allen, Mathew R.; Hayes, H. David (Entrepreneurship Theory and Practice, 2010)
Stewardship theory has been used to explain the culture and relationships within family businesses. Researchers have also demonstrated that stewardship leads to superior family business performance. To date, few empirical analyses have examined the situational mechanisms associated with stewardship in family business. This paper examines the role of the family in explaining stewardship within a family business, including the role of trust, value commitment, and agency. We find that value commitment, trust, and agency perceptions explain a significant portion of stewardship variance for family and nonfamily business employees. We further find that family member employees perceive significantly higher value commitment, trust, and stewardship perceptions and lower agency perceptions in family firm leadership than nonfamily members, suggesting that blood is indeed thicker than water.